Prototype Alat Olah Limbah Cair Laboratorium dengan Prinsip Fisika, Kimia dan Biologi dengan Hasil Akhir yang Aman dibuang dan tidak Mencemari Lingkungan - Saipul Bahri; Sumayya Syarafina; Seli Tamara; Venesa Thalia Putri; Muhammad Naufal Candra Halim; Putri Novitasari (Interest : Jurnal Ilmu Kesehatan, 2020)
Background: Laboratory of Chemical Engineering Environmental Pollution is one of the laboratories that produce liquid waste. However, during this treatment, liquid waste is only stored in a temporary storage area. It will cause part and quality of wastewater produced. It is necessary to research the design of laboratory-scale sports equipment to minimize pollution due to the accumulation of wastewater in conditions without maintenance. Methods: in its design, this tool applied three methods of physical, chemical and biological. This tool will be applied in management using coagulation, electrocoagulation, adsorption, and phytoremediation technologies. Results: This tool can work optimally with an initial capacity of 45 Liters. The parameters tested were pH, TDS, Total Hardness and Lead. The test is carried out to find out the rate of decrease of parameters in each process and the decrease parameter. Conclusion: After testing, it was proven that the biggest decrease in the adsorption process and the result of the calculation of the biggest decrease in TDS was 72.64%. The existence of this tool is expected to overcome the presence of accumulation of liquid waste in the laboratory so that no environmental pollution occurs.